Understanding the Help-Seeking Process Among Second Generation Chinese Canadians Using the Theory of Planned Behaviour: What Is the Role of Culture? - Lee, Andrea Ming-Si (Université d'Ottawa / University of Ottawa, 2016)
The underutilization of mental health services among the Chinese Canadian population is a perpetual problem. The present study examined the help-seeking process among second generation Chinese Canadians using the Theory of Planned Behaviour (TPB). The utility of the TPB was tested using both direct and indirect measures and path analyses were used. The influence of additional variables, including self-stigma, anticipated benefits and risks, and cultural variables such as Asian values, European American values, Chinese identity, Canadian identity, family connectedness and self-concealment were investigated. Two hundred and twelve second generation Chinese Canadians participated in the study. Participants had the option to complete the study questionnaire online or in paper format. Results supported the utilization and application of the TPB in understanding help-seeking intentions and highlighted the differential contribution of attitudes, subjective norms, and perceived behavioural control. The study also supported the notion that perceived behavioural control consists of two inter-related but distinct components: self-efficacy and controllability. Results highlight the importance of self-efficacy in predicting help-seeking intentions among second generation Chinese Canadians. Findings also showed that Asian values, Canadian identity, anticipated benefits and risks, self-concealment, and self-stigma play different roles in predicting attitudes, subjective norms, and perceived behavioural control in the help-seeking process. In sum, results of the present study served as an important step in further understanding the help-seeking process among second generation Chinese Canadians. Implications for research, clinical practice, and future directions are discussed.
Keywords: Help-seeking; Chinese Canadians; Theory of Planned Behaviour